SISTEM PENDUKUNG KEPUTUSAN METODE SIMPLE ADDITIVE WEIGHTING PEMILIHAN BIJI KOPI ROBUSTA BERKUALITAS BERBASIS WEBSITE MENGGUNAKAN PHP 5.6 - Bagus Dwi Fachrizki, Bagus Wahyu Pandhito, Helmi Yoga (Jurnal Teknorama (Informatika dan Teknologi El Rahma), 2024)
This research develops a web-based Decision Support System (DSS) for selecting high-quality Robusta coffee beans at 3A Coffee Shop Lampung. The Simple Additive Weighting (SAW) method is employed, allowing multi-criteria evaluation by considering factors such as taste, aroma, acidity, and price. The system is built using PHP 5.6 and is designed to assist coffee shop managers in determining the best coffee beans. Implementation results indicate that this system effectively enhances the efficiency and accuracy of the coffee bean selection process and facilitates data-driven decision-making